The Methods of Controlling and Training Imaginal Power on the Basis of Islamic Theosophy - Mohsen Torkamaam; Mitra-Zahra poursina (Pizhūhish/hā-yi Falsafī- Kalāmī, 2017)
Muslim philosophers believe that imaginal power has a special status, and plays a crucial role in all domains of human life, particularly in acquiring human perfections. It, however, requires several types of control in order to be corrected and preserved. Having an accurate knowledge of the power and its nature, and on the basis of their philosophical considerations, Muslim philosophers have provided several methods to control and train it in order to provide the ground for human perfection, although they have not dedicated a separated chapter to it in their works. The present paper seeks to gather and elaborate on these methods which have only been hinted in these works. Engaging imaginal power in external senses, controlling it by reason power, doing such activities as meditation, concentration and isolation, acquiring such virtues as truthfulness, balancing constitution, invoking and reciting Quranic verses related to controlling (sukhrah) are among these proposed methods.